Study of Thyroid Hormone Status in Ischemic Heart Disease (IHD) - Lovely, Nasreen Sultana; Begum, Rokeya; Akhter, Qazi Shamima; Sultana, Most. Sabinus; Akhtar, Salina (Journal of Bangladesh Society of Physiologist, 2011)
Background: Thyroid dysfunction especially hypothyroidism is cardiovascular risk factor because of its association with elevated serum total and LDL cholesterol. Objective: To assess the association of thyroid hormone levels with IHD. Methods: This cross-sectional study was carried out on 50 IHD subjects aged 35 to 85 years (Group B), in the Department of Physiology, Dhaka Medical College, Dhaka from of July 2009 to June 2010. For comparison 50 age, sex, and BMI matched apparently healthy subjects (Group-A) were also studied. The study subjects were selected from coronary care unit (CCU) of Cardiology Department & OPD of Dhaka Medical College Hospital, Dhaka. Serum FT3, FT4 and TSH were assessed by radio-immuno assay. Statistical analysis was done by student’s unpaired ‘t’ test and chi-square test as applicable. Result: The mean ±SD of serum FT3 and FT4 were significantly lower and serum TSH was significantly higher in IHD patients than that of healthy subjects (p<0.05). Conclusion: Hypothyroidism occurs in patients suffering from IHD. Key words: Thyroid hormone; IHD. DOI: http://dx.doi.org/10.3329/jbsp.v6i1.8080 J Bangladesh Soc Physiol. 2011 June; 6(1): 27-31